HEALTH AWARENESS AS A PREVENTIVE FACTOR AGAINST SKIN INJURIES IN GYM - Hussein, Emad Abbas; Hussein, Mahmoud Abbas (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Fitness centers have experienced tremendous growth in recent years, becoming a top destination for young people and bodybuilders looking to improve their fitness, build muscle, and enhance their physical performance. Objectives. The study aimed to identify level of health awareness among gym members regarding prevention of skin injuries , and to identify incorrect health behaviors within gyms that contribute to increasing likelihood of skin problems. Method. The researchers adopted descriptive approach with its survey method, as it is the most suitable for nature of the current study. The research sample was selected purposively from original research population, and sample consisted of 100 gym members who met participation requirements, thus achieving an appropriate representation of research population and contributing to achieving the study objectives. Sample was divided into a construction sample consisting of 70 gym members, divided into 6 gym members for pilot application and 64 gym members for statistical analysis, while application sample consisted of 30 gym members. Results. Results of the study showed that general level of health awareness among gym members was very good, reflecting a general positive understanding of importance of preventive behaviors. Conclusion. The researchers recommends adopting regular health awareness programs within gyms that focus on early detection of skin injuries and their transmission mechanisms.